State of democracy in Poland versus environmental protection - Agnieszka Markowska (Central European Economic Journal (CEEJ), 2021)
The paper starts with a review of literature focusing on links between democracy and environmental protection, pointing out a fair weight of scientific evidence that democratic societies on average enjoy a higher level of environmental quality than autocracies. It subsequently provides a quick insight into the recent trends in the state of democracy and the rule of law in Poland as well as a few examples of measures taken concerning environmental policy that have been undertaken after 2015. The paper concludes by expressing concern about certain negative patterns in the Polish environmental policy in the past few years, which seem to be connected to the deficiencies in the rule of law and democracy as observed in Poland. The shrinking space for civil society to participate in democratic governance concerning environmental issues and the excessive appetite of the current government for large infrastructural investments seem to be in contradiction with the European and global strive for sustainable development and tackling climate change. It remains to be seen if the recent negative trends in the Polish environmental policy will have a structural impact on the state of environment in Poland.
Keywords: H41; H83; 330; democracy; environmental policy; Poland; rule of law